Progress in epigenetic modification of ferroptosis involved in chronic obstructive pulmonary disease - CAI Xiaoyu; GAO Feng; HUANG Bin; QIN Huiping (Guangxi Yike Daxue xuebao)
Ferroptosis is a special type of programmed cell death, which is different from autophagy, apoptosis and other modes of death, and characterized by mitochondrial shrinkage, membrane density increase and ridge reduction. The mechanism of ferroptosis is mainly related to the dysregulation of intracellular iron metabolism system, lipid peroxidation, and reduction of glutathione. Chronic obstructive pulmonary disease (COPD) has developed into a serious chronic respiratory disease threatening human health. Chronic inflammation, oxidative stress, and protease/antiprotease imbalance caused by inhalation of tobacco or other atmospheric particles contribute to the development of COPD. Epigenetic modifications affect the heritable expression of genes through histone or nucleic acid sequence modification, and regulate the expression of genes in the ferroptosis-related pathway to amplify or inhibit the role of ferroptosis in COPD. These modifications provide potential therapeutic targets for the disease progression. In this paper, the mechanism of ferroptosis, the relationship between ferroptosis and COPD, and epigenetic modifications regulating ferroptosis and participating in the pathogenesis of COPD are discussed in order to provide reference for the treatment of COPD.